A Brief Study of Methods to Determine the Electrical Resistivity of Materials - Inzamam Khalid (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
Present study deals with the study of methods to calculate the resistivity of materials. Different methods are discussed which determine the resistivity of specific materials on the basis of their shapes and sizes.  Their working, structure, advantages and loopholes are discussed in a brief manner. Materials are categorized according to their magnitude of resistivity. The two probe method is helpful in measuring the resistivity of high resistive samples while four probe methods can be used for materials with low resistance. Pulse probe method measures the resistivity of materials having small physical dimensions. The Montgomery method is useful in finding the individual resistivities of anisotropic materials.